Dynamic response of different bridge piers. Issue 1 (February 2021) - Alaayedi, Husam K.; Aldefae, Asad H.; Shamkhi, Mohammed S.; Humaish, Wissam H.
Abstract: Throughout their construction period and service lifespan, the piers of bridges that built in earthquake zones are susceptible to abrupt earthquake. Thus, during their design period, all the possible circumstances must be taken into consideration because they are strategic infrastructures. Basically, the piers can be considered as the major part of the bridges. This paper presents an experimental work to investigate how the earthquakes influence on the seismic behavior of the selected concrete bridge piers. Physical modeling principals were applied to prepare three models of piers and table of shaking (1-g tests). The piers models were tested under 0.8g waveform for three cases, a rectangular pier constructed on a saturated cohesionless layer of soil, a hexagonal pier constructed over a saturated cohesionless layer and a circular pier installed on saturated cohesionless layer. The obtained results involved the time-acceleration measurement from the accelerometers throughout the shacking, the dynamic earth pressure, and the seismic displacement piers models. Basically, the obtained results of the experiments revealed that the acceleration amplification enhanced greatly at the pier top. The seismic displacement increased sharply because of the strong motion. The rectangular pier exhibited the highest values of the dynamic earth pressure.